Development of a noise prediction software NASEFA and its application in medium-to-high frequency ranges. (May 2015) - Kwon, Hyun-Wung; Hong, Suk-Yoon; Song, Jee-Hun
Highlights: A noise prediction software NASEFA was developed. For effective maintenance, NASEFA is composed of three main modules. NASEFA solves the acoustic energy density and intensity on boundary and in the field. Finally, for the validation of the NASEFA, interior and exterior noise predictions of various structures were performed. Abstract: For the analysis of noise problems in medium-to-high frequency ranges, the energy flow boundary element method (EFBEM) has been studied. EFBEM is numerical analysis method of energy flow analysis (EFA), and solves energy governing equations using a boundary element method in complex structures. Based on EFBEM, a noise prediction software, "noise analysis system by energy flow analysis" (NASEFA), was developed. For effective maintenance, NASEFA is composed of three main modules: the translator, the model converter, and the main solver. The translator changes the FE model to the NASEFA BE model, and the model converter changes the BE model to an EFBE model, including various data, such as structural materials, medium properties, sources, and boundary conditions. NASEFA then solves the acoustic energy density and intensity on boundary and in the field. Moreover, it analyzes interior and exterior noise problems for single and multiple domains in two and three dimensions. Finally, for the validation of the software developed, interior and exterior noise predictions of various structures were performed. The results obtained with NASEFA were compared with those of the commercial SEA program and experiment. From these comparative studies, the usefulness of NASEFA was established.